Penerapan Kekuatan Normatif Uni Eropa di Indonesia - , N GIGIH PRAMONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This undergraduate thesis examines the Normative Power Europe, a concept written by Ian Manners to explain the actorness as well as the ideal objectives of European Union in international politics. This research uses EUâs external action in Indonesia after the fall of Suharto-regime to prove that EU diffuses their norms and values through their actions. The thesis argues that EUâs action in Indonesia is based on three foundation: principle (the action is based on universal or regional norms and principles), action (emphasize on persuasive, dialogues, and symbolic-sanction methods), and impact (good socialization to the society and also has a sustainable impact). This could be seen through several policy, for example Aceh Monitoring Mission where the EU focused on dialogue approach to mediate Indonesia and GAM during the peace-building process